Answer:
-8
Step-by-step explanation:
Given that,
n = -3
r = -8
Now we have to find the value of the given expression.
For that, you have to replace n and r with ( -3 ) and ( -8 ) respectively.
Let us solve now.
−5 + 3 ( −2r + 4n )
-5 + 3 ( -2 × -8 + 4 × -3 )
-2 ( 16 - 12 )
-2 × 4
-8
Let me know if you've any other questions. :-)
- Hi1315
The Intersecting Secant Theorem says
EC × ED = EB × EA
(x+4)(x+4+1) = (x+1)(x+1+11)
(x+4)(x+5)=(x+1)(x+12)
x^2 + 9x + 20 = x^2 + 13 x + 12
8 = 4x
x = 2
Check:
6(7)=42
3(14)=42, good
Answer: 2
None of the numbers on the list of choices that you posted
with the question meets those conditions.
Answer:
Step-by-step explanation: